REKONSEPTUALISASI PERAN INTERMEDIASI PERBANKAN SYARIAH DALAM PEMBERDAYAAN EKONOMI UMAT: TINJAUAN SISTEMATIS PENDEKATAN PEMBIAYAAN MIKRO DI INDONESIA - musliadi, suci ramadhani; Emily Nur Saidy (IAIN Parepare, 2025)
ABSTRACT Islamic banking plays a crucial role as a financial intermediary that not only prioritizes profit but also aims to empower the economic well-being of the ummah. However, in practice, Islamic banks in Indonesia have largely focused on consumptive financing and have yet to fully engage with the microenterprise sector, which constitutes the backbone of the ummah's economy. This study seeks to reconceptualize the intermediary function of Islamic banking through a microfinance lens within the context of an economic transition era characterized by digitalization, socio-economic transformation, and widening financial access inequality. Employing a qualitative-descriptive approach through library research, the study analyzes academic literature, secondary data, and relevant policy frameworks. The findings highlight the strategic potential of Islamic microfinance in reinforcing the ummah’s economy by upholding principles of justice, sustainability, and inclusivity. The implementation of integrated Islamic microfinance models—leveraging Islamic social funds (zakat, infaq, sadaqah, and waqf) and fostering collaboration between Islamic banks and Islamic microfinance institutions (BMTs/LKMS)—can significantly enhance the effectiveness of financial intermediation. The study recommends a paradigm shift from a bank-centric to a community-centric intermediation model, strengthened microfinance regulatory frameworks, and the digitalization of microfinance services to expand outreach to underserved economic segments in a more inclusive and sustainable manner. ABSTRAK Perbankan syariah memiliki peran penting sebagai lembaga intermediasi yang tidak hanya berorientasi pada keuntungan, tetapi juga pada pemberdayaan ekonomi umat. Namun, dalam praktiknya, perbankan syariah di Indonesia masih cenderung terfokus pada pembiayaan konsumtif dan belum sepenuhnya menjangkau sektor usaha mikro yang menjadi tulang punggung ekonomi umat. Penelitian ini bertujuan untuk merekonseptualisasi peran intermediasi perbankan syariah melalui pendekatan pembiayaan mikro dalam konteks era transisi ekonomi yang ditandai oleh digitalisasi, perubahan struktur sosial-ekonomi, dan meningkatnya ketimpangan akses keuangan. Metode yang digunakan adalah studi pustaka (library research) dengan pendekatan kualitatif deskriptif melalui analisis terhadap literatur akademik, data sekunder, dan kebijakan terkait. Hasil kajian menunjukkan bahwa pembiayaan mikro syariah berpotensi menjadi instrumen strategis dalam memperkuat ekonomi umat melalui prinsip keadilan, keberlanjutan, dan inklusi. Implementasi model pembiayaan mikro syariah yang terpadu dengan dana sosial Islam (zakat, infak, sedekah, wakaf) dan kolaborasi antara bank syariah dan lembaga keuangan mikro syariah (BMT/LKMS) dapat meningkatkan efektivitas intermediasi keuangan syariah. Implikasi dari studi ini merekomendasikan perlunya pergeseran paradigma intermediasi dari pendekatan bank-sentris ke umat-sentris, penguatan kerangka regulasi pembiayaan mikro, serta digitalisasi sistem layanan untuk menjangkau segmen ekonomi bawah secara lebih luas dan berkelanjutan.